Extreme bounds of sovereign defaults - Zeaiter, Hussein (2016)
This paper investigates the determinants of sovereign debt defaults using Leamer's (1983) extreme bounds analysis (EBA). The EBA approach is applied for the indebted countries in the MENA region during the 1970 to 2010 period to determine whether economic and political factors are robust or fragile. This study finds that debt accumulated arrears can be perceived as a signal of default and can warn MENA countries to prevent total failure or at least alleviate the severity of the default. This paper is important for policy makers in the MENA region when seeking to reduce the probability of default. Many recommendations are offered to the indebted MENA countries. For example, they should (1) attract more foreign reserves through adjusting domestic policies and regulations of investment, (2) enact proactive fiscal policies, and (3) fight corruption and promote democracy.